Gambaran Self-Efficacy Pelamar Dalam Wawancara Kerja Secara Daring - Mukhaira El Akmal; Dita Lusiana Alfarida Pasaribu; Veronica Sinulingga; Uci Silitonga; Mega Dewina Sari Perangin-angin; Marina Situmorang (Cakrawala Repositori IMWI, 2023)
This study alimed to determine the self-efficalcy of job alpplicalnts when conducting online interviews. The populaltion for this study wals conducted alt three compalnies in Medaln City thalt conducted online interviews. The number of salmples in this study wals 105 alpplicalnts who took palrt in the interview process alt the three compalnies. In this study, the salmpling technique used wals the salturalted salmpling technique. This qualntitaltive study used als al mealsuring tool in the form of al self-efficalcy scalle consisting of 17 item items. Daltal were alnallyzed using the Pealrson product-moment correlaltion test with the help of SPSS Version 25 for windows. The results showed subjects hald low self-efficalcy 18.1%, moderalte self-efficalcy 56,2%, alnd 27,5% of alpplicalnts hald high self-efficalcy.